IMPROVEMENT OF THE REDLICH-KWONG EQUATION OF STATE BY MODIFICATION OF CO-VOLUME PARAMETER - Ratnawati Ratnawati (Dept. of Chemical Engineering, Diponegoro University, 2010)
Cubic equations of state are widely used in phase-equilibrium calculations because of their simplicity and accuracy. Most equations of states are not accurate enough for predicting density of liquid and dense gas. A modification on the Redlich-Kwong (RK) equation of state is developed. Parameter b is modified by introducing a new parameter,b, which is a function of molecular weight and temperature. The modification gives a significant improvement over the original RK equation for predicting density. For 6538 data points of 27 compounds, the proposed equation gives only 2.8% of average absolute deviation (AAD), while the original RK and the Soave-Redlich-Kwong (SRK) equations give 11.4% and 11.7%, respectively. The proposed modification improves the performance of the RK equation for predicting vapor pressure as well. For 2829 data points of 94 compounds, the proposed modification lowers the AAD of the RK equation from 1460% down to 30.8%. It is comparable to the famous SRK equation, which give 5.8% of AAD. The advantage of the proposed equation is that it uses only critical pressure and temperature as other equations of states do, and molecular weight, which is easily calculated. Another advantage is that the proposed equation simpler than the SRK equation of state.